Effect of adsorbants on in vitro biohydrogenation of 22:6n-3 by mixed cultures of rumen microorganisms. (11th March 2016) - Escobar, M.; Vlaeminck, B.; Jeyanathan, J.; Thanh, L. P.; Shingfield, K. J.; Wallace, R. J.; Fievez, V.
Abstract : Studies on microbial biohydrogenation of fatty acids in the rumen are of importance as this process lowers the availability of nutritionally beneficial unsaturated fatty acids for incorporation into meat and milk but also might result in the accumulation of biologically active intermediates. The impact was studied of adsorption of 22:6n-3 (DHA) to particulate material on its disappearance during 24 h in vitro batch incubations with rumen inoculum. Four adsorbants were used in two doses (1 and 5 mg/ml of mucin, gum arabic, bentonite or silicic acid). In addition, the distribution of 22:6n-3 in the pellet and supernatant of diluted rumen fluid was measured. Bentonite and silicic acid did not alter the distribution of 22:6n-3 between pellet and supernatant nor increased the disappearance of 22:6n-3 during the incubation. Both mucin and gum arabic increased the recovery of 22:6n-3 in the supernatant, indicating that these compounds lowered the adsorption of the fatty acid to ruminal particles. This was associated with an increased disappearance of 22:6n-3, when initial 22:6n-3 was 0.06 or 0.10 mg/ml, and an increased formation of 22:0, when initial 22:6n-3 was 0.02 mg/ml, during the 24 h batch culture experiment. Addition of gum arabic to pure cultures of Butyrivibrio fibrisolvens or Butyrivibrio proteoclasticus did not negate the inhibitory effect of 22:6n-3 on growth. As both mucin and gum arabic provide fermentable substrate for ruminal bacteria, an additional experiment was performed in which mucin and gum arabic were replaced by equal amounts of starch, cellulose or xylan. No differences in disappearance of 22:6n-3 were observed, suggesting that the stimulatory effect of mucin and gum arabic on disappearance of 22:6n-3 most probably is not due to provision of an alternative site of adsorption but related to stimulation of bacterial growth. A relatively high proportion of 22:6n-3 can be reduced to 22:0 provided the initial concentration is low.